2013
DOI: 10.1016/j.neuron.2013.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic VCP Mutations Induce Mitochondrial Uncoupling and Reduced ATP Levels

Abstract: SummaryValosin-containing protein (VCP) is a highly expressed member of the type II AAA+ ATPase family. VCP mutations are the cause of inclusion body myopathy, Paget’s disease of the bone, and frontotemporal dementia (IBMPFD) and they account for 1%–2% of familial amyotrophic lateral sclerosis (ALS). Using fibroblasts from patients carrying three independent pathogenic mutations in the VCP gene, we show that VCP deficiency causes profound mitochondrial uncoupling leading to decreased mitochondrial membrane pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 39 publications
7
110
0
2
Order By: Relevance
“…The pathology of VCP-associated degenerative diseases features ubiquitin-positive inclusions. Although some of the pathogenic VCP mutations have been shown to affect the ATPase activities (11, 12) or mitochondrial function (13,14), the effects of these mutations in protein homeostasis, especially in the cellular stress response associated with the development of degenerative diseases, are unclear. As weakened cellular stress response contribute to aging and the development of neurodegenerative diseases (15-17), it will be of great interest to determine whether the pathogenic mutations in VCP also affect cellular stress response.…”
mentioning
confidence: 99%
“…The pathology of VCP-associated degenerative diseases features ubiquitin-positive inclusions. Although some of the pathogenic VCP mutations have been shown to affect the ATPase activities (11, 12) or mitochondrial function (13,14), the effects of these mutations in protein homeostasis, especially in the cellular stress response associated with the development of degenerative diseases, are unclear. As weakened cellular stress response contribute to aging and the development of neurodegenerative diseases (15-17), it will be of great interest to determine whether the pathogenic mutations in VCP also affect cellular stress response.…”
mentioning
confidence: 99%
“…Moreover, our group has previously reported a complex I deficiency in a patient with FTLD [22]. Other studies have shown that alterations in the VCP gene induced mitochondrial uncoupling that has been observed in different neurodegenerative diseases [14]. However, in our cohort, no alterations have been associated with this gene.…”
Section: Discussionmentioning
confidence: 50%
“…Several mutations in nuclear genes have been associated with the different variants of FTLD, namely microtubule-associated protein tau and progranulin genes and, less frequently, valosin-containing protein (VCP), charged multivesicular body protein 2B, TAR-DNA binding protein and fused in sarcoma genes [5,13]. Mutations in the VCP gene induce mitochondrial dysfunction leading to lower ATP levels due to reduced ATP production [14]. Some studies have identified a noncoding expanded GGGGCC hexanucleotide repeat in the C9orf72 gene, linked to chromosome 9p21, that has been strongly associated with FTLD/ALS [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a missense mutation in the CHCHD10 gene encoding a mitochondrial protein apparently important for mitochondrial structure and function has recently been associated with ALS and frontotemporal dementia, and muscle fibers from these patients exhibit mitochondrial abnormalities [99]. In addition to the well-characterized mitochondrial abnormalities reported in multiple mouse models of ALS involving overexpression of mutated SOD1 [97], mitochondrial abnormalities have also been reported in mutated VCP [100,101], TDP-43 [102,103] and FUS [104] models. This appears to be a very early pathological feature of transgenic ALS model mice: abnormal mitochondria are evident in mice expressing mutant SOD1 before symptom onset [102,105,106].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%